DFT‐D4 counterparts of leading meta‐generalized‐gradient approximation and hybrid density functionals for energetics and geometries. Issue 30 (1st September 2020) - Najibi, Asim; Goerigk, Lars
Abstract: Previously, we introduced DFT‐D3(BJ) ω B97X‐V and ω B97M‐V functionals and assessed them for the GMTKN55 database [Najibi and Goerigk, J Chem. Theory Comput. 2018, 14, 5725]. In this study, we present DFT‐D4 damping parameters to build the DFT‐D4 counterparts of these functionals and assess these in comparison. We extend our analysis beyond GMTKN55 and especially turn our attention to enzymatically catalyzed and metal–organic reactions. We find that B97M‐D4 is now the second‐best performing meta‐generalized‐gradient approximation functional for the GMTKN55 database and it can provide noticeably better organometallic reaction energies compared to B97M‐D3(BJ). Moreover, the aforementioned DFT‐D3(BJ)‐based functionals have not been thoroughly assessed for geometries and herein we close this gap by analyzing geometries of noncovalently bound dimers and trimers, peptide conformers, water hexamers and transition‐metal complexes. We find that several of the B97(M)‐based methods—particularly the DFT‐D4 versions—surpass the accuracy of previously studied methods for peptide conformer, water hexamer, and transition‐metal complex geometries, making them safe‐to‐use, cost‐efficient alternatives to the original methods. The DFT‐D4 variants can be easily used with ORCA4.1 and above. Abstract : DFT‐D4 ω B97X‐V, and ω B97M‐V are presented and shown to be accurate, cost‐efficient, and reliable methods for both energetic properties and geometries.